ASSOCIATION OF PHYSICIAN BURNOUT WITH HEADACHE AND LOW BACK PAIN DURING PANDEMIC COVID-19 - Kharisma Ridho Husodo; Dea Hadfina Kartika Sari; Lintang Daru Jati; Airin Angelina (MNJ (Malang Neurology Journal), 2023)
Background: Physician burnout is a common problem seen in health workers, especially doctors and it is characterized by emotional exhaustion, depersonalization, and reduced personal accomplishment in daily work. The pandemic of Corona Virus Disease 2019 (COVID-19) causes an increase in the workload among doctors which will affect the incidence of Burnout. Burnout not only includes psychological problems, but also has a risk for physical disorders including pain disorders. Objective: To investigate the association of burnout level with headache and low back pain among physicians at Yogyakarta Islamic Hospital PDHI. Methods: This research design was a descriptive analytic study with a cross-sectional design. The subjects in this study were 46 doctors who worked at the Yogyakarta Islamic Hospital PDHI. Burnout levels were assessed using the Maslach Burnout Inventory (MBI) test. The incidence of headache and its impact on daily activities were assessed using the Headache Impact Test (HIT-6) questionnaire while Low Back Pain was assessed using Oswestry Disability Index (ODI). Results: Among burnout parameters, depersonalization was the most influential parameter which caused burnout. COVID-19 pandemic gave more impact to burnout level. The headache and low back pain incidence were 39,1% (18 subjects) and 43,4% (20 subjects) respectively. There were significant correlations between headache and every burnout parameter. Low back pain also had significant correlations to each burnout parameters. Conclusion: There was association of Burnout level with headache and low back pain incidence among physicians.